2017
DOI: 10.1021/acsami.7b08439
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Jet Treatment of Poly-ε-caprolactone Polymer Solutions To Improve Electrospinning

Abstract: An atmospheric pressure plasma jet (APPJ) specifically designed for liquid treatment has been used in this work to improve the electrospinnability of a 5 w/v % solution of poly-ε-caprolactone (PCL) in a mixture of chloroform and N,N-dimethylformamide. Untreated PCL solutions were found to result in nonuniform fibers containing a large number of beads, whereas plasma-treated solutions (exposure time of 2-5 min) enabled the generation of beadless, uniform nanofibers with an average diameter of 450 nm. This enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 42 publications
2
56
0
Order By: Relevance
“…The plasma source used in this work to treat PEOT/PBT polymer solutions is an APPJ specifically designed for liquid treatment and is schematically represented in Figure 1 . The setup was already described in detail in previous work . In short, the plasma is generated inside a thin quartz capillary fed by an argon flow.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The plasma source used in this work to treat PEOT/PBT polymer solutions is an APPJ specifically designed for liquid treatment and is schematically represented in Figure 1 . The setup was already described in detail in previous work . In short, the plasma is generated inside a thin quartz capillary fed by an argon flow.…”
Section: Methodsmentioning
confidence: 99%
“…followed a similar strategy, using an atmospheric pressure plasma jet (APPJ) to treat polylactic acid dissolved in dichloromethane and observed 100% bead‐free fibers . In our research group, an extensive study on the effects of NTP exposure on a solution of PCL or PLLA in CHCl 3 and DMF was recently performed . It was found that the plasma was responsible for improving the conductivity of the polymer solution as well as changing the viscosity and pH via the generation of new chemical species without damaging the macromolecular structure of the polymer …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations